PENGEMBANGAN LKPD ELEKTRONIK BERBASIS BERPIKIR KRITIS DENGAN PBL PADA MATERI PERUBAHAN LINGKUNGAN KELAS X - Syahmila Nanda Fani; Fitra Suzanti; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This development aims to produce an Electronic LKPD Based on Critical Thinking with PBL on quality Class X Environmental Change Materials. The research was carried out at the Biology Education Study Program, FKIP Riau University and SMA Negeri 1 Teluk Kuantan from January to March 2022. The research subject was KD 3. 6 material on environmental changes in class X SMA. The type of research used is the ADDIE Research and Development model. The instruments used are in the form of validation sheets and response questionnaires. The validation sheet consists of 4 aspects, namely aspects of content feasibility, linguistic aspects, presentation aspects, and graphic aspects. The average validation result of the electronic LKPD based on the four aspects is 3.90 with a very valid category. The four aspects include content feasibility aspects 4, linguistic aspects 3.88, presentation aspects 3.92, and graphic aspects 3.81. The results of the limited trial phase I got an average score of 3.91 very good categories. While the results of the limited trial phase II got an average score of 3.92 in the very good category. The results showed that the electronic LKPD based on critical thinking with PBL on the material for environmental change in class X was of high quality and suitable to be used as a learning resource.Key Words: Electronic LKPD, Critical Thinking, PBL, Environmental Change.